2022
DOI: 10.1038/s41467-022-28523-1
|View full text |Cite
|
Sign up to set email alerts
|

T-cell dysfunction in the glioblastoma microenvironment is mediated by myeloid cells releasing interleukin-10

Abstract: Despite recent advances in cancer immunotherapy, certain tumor types, such as Glioblastomas, are highly resistant due to their tumor microenvironment disabling the anti-tumor immune response. Here we show, by applying an in-silico multidimensional model integrating spatially resolved and single-cell gene expression data of 45,615 immune cells from 12 tumor samples, that a subset of Interleukin-10-releasing HMOX1+ myeloid cells, spatially localizing to mesenchymal-like tumor regions, drive T-cell exhaustion and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
124
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(133 citation statements)
references
References 74 publications
9
124
0
Order By: Relevance
“…With the continuing refinement of spatial multiplex imaging technologies, detailed characterizations of the immune proteome within the TME have become possible. Using these techniques, one study found that myeloid cells localized to mesenchymal-like regions of GBM drive T cell exhaustion via IL-10 release, and that this T cell function was rescued with Janus kinase-signal transducer and activator of transcription (JAK/STAT) inhibition, providing a potential therapeutic opportunity ( 57 ). These techniques are allowing for the discovery of wider and more heterogeneous populations of immune cells with newly identified, previously unexploited cell phenotypes with distinct functions that influence tumor biology.…”
Section: Discussionmentioning
confidence: 99%
“…With the continuing refinement of spatial multiplex imaging technologies, detailed characterizations of the immune proteome within the TME have become possible. Using these techniques, one study found that myeloid cells localized to mesenchymal-like regions of GBM drive T cell exhaustion via IL-10 release, and that this T cell function was rescued with Janus kinase-signal transducer and activator of transcription (JAK/STAT) inhibition, providing a potential therapeutic opportunity ( 57 ). These techniques are allowing for the discovery of wider and more heterogeneous populations of immune cells with newly identified, previously unexploited cell phenotypes with distinct functions that influence tumor biology.…”
Section: Discussionmentioning
confidence: 99%
“…While previous therapeutic strategies have focused on the depletion of these cell types, there is now increasing efforts in reprogramming immunosuppressive microenvironments (Coniglio et al, 2012; Pyonteck et al, 2013; Quail and Joyce, 2017). These reprogramming strategies have largely focused on skewing the phenotype of bbm from an immunosuppressive M2-like to a proinflammatory M1-like phenotype assuming that immunosuppression by bbm is driven by soluble factors such as IL10 or TGFb (Poon et al, 2017; Ravi et al, 2022). MHCII expression is considered a marker of proinflammatory M1-like bbm but the functional relevance of MHCII has remained ill-understood.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IL10, which was found in our study to be upregulated in regrown tumors compared with primary implanted tumors, was shown to promote glioma cell growth and invasion [ 32 , 33 ] Moreover, IL-10 was shown to suppress proliferation, cytokine production, and migration of effector T-cells, driving T-cell exhaustion and thus creating an immunosuppressing environment in the tumor [ 34 , 35 ]. Increased expression of IL-10 in GBM patients was correlated with brief survival [ 36 ].…”
Section: Discussionmentioning
confidence: 99%